Hubungan Kepercayaan Pasien dan Kualitas Pelayanan dengan Imunisasi Dasar Lengkap di Kelurahan Sekanak Raya Wilayah Kerja UPTD Puskesmas Belakang Padang - Geda Lilova Maja Nanda; Nelli Roza; Huzaima Huzaima (Jurnal Kesehatan Amanah, 2024)
Background: The global under-five mortality rate in 2021 is 38 deaths per 1000 live births. Andersen's theory consists of three main components that influence the use of health services, namely predisposing characteristics, enabling resources, need and health service use. Objective: To determine the relationship between patient trust and service quality with complete basic immunization in Sekanak Raya Village. Method: This research is a quantitative study, with an analytical observational design with a cross sectional approach. The population in this study were mothers who had children in Sekanak Raya Village. Data collection tools use observation sheets and questionnaires. Data analysis used the chi-square test. Results: The majority of underdog mothers who believe in complete basic immunization status are 15 people (100%), while the underdog mothers who assess the quality of service are good with complete basic immunization status are 18 people (100%). The results of the chi square statistical test for patient confidence obtained a p-value of 0.022 < 0.05; and for service quality, the p value was 0.004 <0.05. Conclusion: There is a significant relationship between patient trust and quality of service with complete basic immunization in Sekanak Raya Village, UPTD Working Area, Puskesmas, Rear Padang, Batam City in 2024.